1993
DOI: 10.1115/1.2906697
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Stability and Response Analysis of a Nonlinear Rotor System With Mass Unbalance and Side Load

Abstract: The stability of steady-state synchronous and nonsynchronous response of a nonlinear rotor system supported by squeeze-film dampers is investigated. The nonlinear differential equations that govern the motion of rotor bearing systems are obtained by using the Generalized Polynomial Expansion Method. The steady-state response of the system is obtained by using the hybrid numerical method, which combines the merits of the harmonic balance and collocation methods. The stability of system response is examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They also used the properties of the Rayleigh quotient to calculate the critical speed of the system. Shiau et al [11] reported on the use of GPEM to study the nonlinear problem. The stability of the steady-state responses of a rotor supported by the nonlinear squeeze film dampers was investigated.…”
Section: Generalized Polynomial Expansion Methodsmentioning
confidence: 99%
“…They also used the properties of the Rayleigh quotient to calculate the critical speed of the system. Shiau et al [11] reported on the use of GPEM to study the nonlinear problem. The stability of the steady-state responses of a rotor supported by the nonlinear squeeze film dampers was investigated.…”
Section: Generalized Polynomial Expansion Methodsmentioning
confidence: 99%